A study on the express courier industry - Lim, Tze Ming. (2008)
The objective of this dissertation is to examine the commercial development in the express courier industry by understanding: a) The strategic usage of Information Technology (IT) within the express courier industry and b) the industry structure through performing strategic management model analysis and case studies.